The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1055/a-1755-4700
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed Acceptorless Dehydrogenative Coupling of 2-Aminoarylmethanols with Amides or Nitriles to Synthesize Quinazolines

Abstract: An efficient iridium-catalyzed acceptorless dehydrogenative coupling (ADC) reaction for the preparation of various quinazolines from 2-aminoarylmethanols and amides or nitriles had been developed. A wide range of substituted 2-aminobenzyl alcohols and (hetero)aryl or alkyl benzamides and nitriles were well compatible to afford various quinazolines in excellent yields. This new strategy merits the high atom-economy, mild reaction condition, simple operation and suited to a variety of substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Furthermore, in 2019, Gargi et al 20 reported the synthesis of 2-aminoquinolines, quinazolines, and quinolines by dehydrogenative coupling, intramolecular cyclodehydration, and condensation using Ni ( ii ) catalysis (Scheme 2b). Shui et al 21 in 2022 reported the synthesis of quinazolines using acceptorless dehydrogenative coupling with a homogeneous iridium catalyst, followed by alcohol dehydrogenation, condensation, and cyclization (Scheme 2c). Despite numerous reports of alcohol oxidation to carbonyl compounds and its subsequent utility for the synthesis of heterocyclic moieties under homogeneous conditions, these methods have several drawbacks (a) use of expensive second-row transition metal catalysts (b) contamination of final product under homogeneous conditions, and (c) no catalyst recyclability.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in 2019, Gargi et al 20 reported the synthesis of 2-aminoquinolines, quinazolines, and quinolines by dehydrogenative coupling, intramolecular cyclodehydration, and condensation using Ni ( ii ) catalysis (Scheme 2b). Shui et al 21 in 2022 reported the synthesis of quinazolines using acceptorless dehydrogenative coupling with a homogeneous iridium catalyst, followed by alcohol dehydrogenation, condensation, and cyclization (Scheme 2c). Despite numerous reports of alcohol oxidation to carbonyl compounds and its subsequent utility for the synthesis of heterocyclic moieties under homogeneous conditions, these methods have several drawbacks (a) use of expensive second-row transition metal catalysts (b) contamination of final product under homogeneous conditions, and (c) no catalyst recyclability.…”
Section: Resultsmentioning
confidence: 99%
“…Aromatic secondary alcohols substituted with electron-donating groups led to higher chemoselectivities and yields of the products (Table 3, entries 2-5) than the aryl secondary alcohols and aminobenzyl alcohol with electron-withdrawing groups (Table 3, entries 8, 11, 12, 15, 16, 19, 20, 23, and 24). Meanwhile, the heteroaromatic secondary alcohols 2i-n could also be employed in the cyclometalated iridium-catalyzed system obtaining the products 3ai-an with excellent yield and chemoselectivity (Table 3, entries [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The results showed that the yield and chemoselectivity was higher when the heteroaromatic secondary alcohols and aminobenzyl alcohols have electron-donating groups (Table 3, entries 27, 30, 31, 34, 35, 39, and 42).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies [39][40][41][42], we found that cyclometalated iridium catalysts can effectively catalyze the dehydrogenation of alcohols to produce carbonyl compounds and hydrogen gas. Therefore, we used cyclometalated iridium complex (TC-6) to catalyze the ADC reaction of o-aminobenzyl alcohols 1 and aryl/heteroaryl/alkyl secondary alcohols 2 that allowed for the efficient synthesis of a series of quinolines 3 (up to 95% yield and >99:1 selectivity) (Figure 2).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Very recently, Luo et al ( 2022) reported an efficient iridiumcatalyzed ADC reaction between 2-aminoarylmethanols 20 and amides 24/nitriles 35 in the presence of t-BuOK/KOH in 1,4dioxane at 80 °C-100 °C to provide quinazolines 155 (Scheme 22E). (Shui et al, 2022) Excellent yields of up to 99% were achieved by employing a variety of substituted 2-aminobenzyl alcohols 20, (hetero)aryl or alkyl benzamides 24, and nitriles 35. The salient features of this protocol are mild reaction conditions, a simple operation procedure, and high atom economy.…”
Section: Iridiummentioning
confidence: 99%